Heterogeneity of Posttraumatic Stress Disorder Symptoms in Croatian War Veterans: Retrospective Study - Begić, Dražen (Array, 2007)
Aim To determine the relationship between the intensity of combat-related posttraumatic stress disorder (PTSD) and predominating symptoms. Method The study included 151 Croatian war veterans with PTSD aged 38.3± ; 7.3 years. The veterans were psychologically tested with Mississippi Scale for Combat-related PTSD (M-PTSD), Questionnaire on Traumatic Combat and War Experiences (USTBI-M), and Minnesota Multiphasic Personality Inventory-version 201 (MMPI-201). M-PTSD was used to measure severity of PTSD symptoms, USTBI-M measured the exposure to stressful events, and MMPI-201 measured general symptoms. Discriminant analysis was performed. Results The discriminative analysis revealed that the group with lower PTSD disorder had higher scores on scales D, Hs, and Hy, whereas the group with the higher PTSD intensity had also clinically significantly “ elevated” Pt, Sc, and Pa scales, with the Pa scale as the highest. It was possible to differentiate study participants with different PTSD intensity on the basis of their MMPI profile. Conclusion The two groups of war veterans with different PTSD intensity differed in their MMPI-201 profile. More intense PTSD was associated with externalized symptoms, such as aggression, acting-out, hostility, and mistrust, whereas less intensive PTSD was associated with mostly depressive symptoms.